Dampak Kebijakan Pandemi Covid-19 Pada Masjid Raya - Muhammad Saerozi (Profesional Muda Cendekia Publishing, 2021)
The Covid-19 pandemic that has hit Indonesia since March 2109 has an impact on all aspects of life, including in this study the impact on mosque cash. This study aims to analyze the trend of obtaining mosque cash funds at the Istiqomah Ungaran Grand Mosque before and during the covid-19 pandemic, if there is a decline then what causes the decline to occur and what philanthropic strategies are made by mosque administrators to optimize the mosque's cash funds. This research was completed by using a mixed method qualitative and quantitative with data collection methods through observation, interviews, documentation and group discussion forums (FGD). This study found that a significant decrease occurred in the cash fund of the Great Mosque of Istiqomah Ungaran due to the reduced activities organized by the mosque. The strategy made by the administrators of the Istiqomah Grand Mosque in Ungaran is with online recitations as well as infaq payments and online Istiqomah RA and SD Istiqomah tuition payments.